MINI DENTAL IMPLANTS: ADVANTAGES, LIMITATIONS AND CLINICAL APPLICABILITY - Iulian Constantin; Irina Adriana Beuran; Norina Consuela Forna; Anton Knieling; Doriana Agop Forna; Cristian-Constantin Budacu (Romanian Journal of Oral Rehabilitation)
Mini dental implants offer an effective and minimally invasive alternative for edentulous patients, especially those with advanced bone resorption, who are not ideal candidates for conventional implants. This review analyzes the advantages and limitations of mini-implants, emphasizing their clinical applicability in the stabilization of mobile prostheses and temporary fixed restorations. While mini-implants have many benefits, such as reduced costs, simplified procedure, and shorter recovery time, they also have important limitations, including their reduced ability to sustain high occlusal forces and inferior long-term durability. Advanced biomaterials, such as titanium alloys, are essential for the success of mini-implants, ensuring osseointegration and reducing the risk of inflammation. In addition, essential oils, with antimicrobial and anti-inflammatory properties, help maintain peri-implant health, preventing infections and peri-implant complications. The integrative approach, which combines the use of biomaterials and essential oils, can significantly improve the stability and success rate of dental mini implants, providing patients with a durable and functional solution for dental restoration. This analysis emphasizes the importance of the appropriate selection of treatment for each patient according to clinical needs and aesthetic requirements.